PEMBERDAYAAN MASYARAKAT DALAM MENINGKATKAN SEMANGAT KEWIRAUSAHAAN DI DESA SEBENTE - Usman Usman; Veneranda Rini Hapsari; Rissa Ayustia (Politeknik Negeri Ambon, 2020)
The problem of poverty is not only due to the pressure of economic factors but there are other factors that are more influential, namely the very low human resource factor of farmers. The problems of unemployment and poverty remain problems that have not been resolved properly in the Indonesian government. Unemployment in Indonesia, one of which is the unavailability of jobs for new graduates and lack of adequate human resources. The purpose of this study is to describe how big the role of village heads is in increasing the entrepreneurial spirit for people's lives, in order to improve the welfare of economic life for As a real effort that can be made by the Village Head is to conduct various trainings and assistance for farmers so that they can have skills that they can use, as a provision for them to work. The research method used is descriptive qualitative method. Result: The spirit of service shown by the village head and the approach of a leader figure who is able to provide a good example to the community so that it can influence changes in the mindset of the community itself. Changes in the mindset of the community can occur by conducting a lot of training and mentoring. Conclusion: In this study, the findings are described in several parts: The spirit of service and the approach of a leader who is able to set a good example to the community turns out to influence changes in the mindset of the community for the better. As a solution to the problem of lack of adequate human resources, a lot of training and mentoring can be done.